Medida socioeducativa em meio aberto: vivências e perspectivas de adolescentes e jovens - Cavalcante, Luciana Paiva (2019)
The purpose of the present dissertation was to analyze the living experience of adolescents who committed infractions and accomplished socio-educational measures in an open environment in the city of João Pessoa, capital of the state of Paraíba, Brazil, with assistance and follow-up of the teams of CREAS/PAEFI. The research has as the starting hypothesis that even regarding the efforts of professional teams and the advancement of the Brazilian legislation concerning the responsibility and the pedagogical character of the socio-educational measures in an open environment, these measures are not yet sufficient to ensure that adolescents and young people do not recidivate to practice infractions. These acts difficult and/or prevent their social reintegration, where political and structural factors are among the main reasons for the low satisfactory outcome of these measures. This research uses quantitative data to measure and characterize the object of study, and adopts a primarily qualitative approach based on the adolescents’ statements about their living experiences and perspectives in the process of the accomplishment of the measures. In the examination of the interviews, it was used the procedure of content analysis of previously established categories and subcategories. From an epistemological point of view, the study is based on dialectical materialism regarding the examination of the object of research as a reflection of the contradictions originated from the economic base of the capitalist society with a deep inequity and the articulated configuration of a minimal State in the provision of social policies with a Penal State as an instrument of social violence contention. From the testimonies of adolescents and young people who described their experiences, challenges, and perspectives, it was possible to envisage that the absence of articulated actions among the different sectors involved in the attainment of the socio-educational measures and a set of complementary public policies, specially, educational policies that combat the low schooling of these young people, reduce the possibilities of their social reintegration as citizens, and prove to be the main cause of many of the recidivism.